ANALYSIS OF THE RELATIONSHIP OF PARENTING PATTERNS ON STUDENTS' LEARNING MOTIVATION - Fatma Dewani Harahap (Jurnal Scientia, 2022)
This study aims to describe and examine the magnitude of the relationship between parental education patterns and learning motivation of third grade students at SD Negeri 100760 Bargottopong Jae, Paluta Regency. This research includes qualitative research. This study used a sample of 6 third grade students of SD Negeri Bargottopong Jae. The data collection used using the methods of observation, interviews and documents. The data analysis technique used is descriptive analysis. The results showed that there were differences in parenting applied by parents. The application of democratic parenting is mostly applied by parents, then authoritarian and permissive parenting. There are 4 parents who apply democratic parenting, 1 parent with authoritarian parenting and 1 parent with permissive parenting. Students with authoritarian and democratic parenting have good and sufficient motivation to learn. Meanwhile, students with permissive parenting have less motivation. Based on the research, it can be concluded that parenting and parental participation have an effect on students' learning motivation.